Endocrine manifestations and management of Prader-Willi syndrome - Emerick, Jill E (BioMed Central, 2013)
Prader-Willi syndrome (PWS) is a complex genetic disorder, caused by lack of expression of genes on the paternally inherited chromosome 15q11.2-q13. In infancy it is characterized by hypotonia with poor suck resulting in failure to thrive. As the child ages, other manifestations such as developmental delay, cognitive disability, and behavior problems become evident. Hypothalamic dysfunction has been implicated in many manifestations of this syndrome including hyperphagia, temperature instability, high pain threshold, sleep disordered breathing, and multiple endocrine abnormalities. These include growth hormone deficiency, central adrenal insufficiency, hypogonadism, hypothyroidism, and complications of obesity such as type 2 diabetes mellitus. This review summarizes the recent literature investigating optimal screening and treatment of endocrine abnormalities associated with PWS, and provides an update on nutrition and food-related behavioral intervention. The standard of care regarding growth hormone therapy and surveillance for potential side effects, the potential for central adrenal insufficiency, evaluation for and treatment of hypogonadism in males and females, and the prevalence and screening recommendations for hypothyroidism and diabetes are covered in detail. PWS is a genetic syndrome in which early diagnosis and careful attention to detail regarding all the potential endocrine and behavioral manifestations can lead to a significant improvement in health and developmental outcomes. Thus, the important role of the provider caring for the child with PWS cannot be overstated.